Choroidal Metastasis Secondary to Testicular Mature Teratoma: A Case Report - Bata, Bashar M. (Ocul Oncol Pathol, 2021)
We report a case of a choroidal metastasis secondary to testicular mature teratoma, a subtype of non-seminoma germ cell tumours, in a young adult male. The choroidal metastasis was treated successfully with bleomycin, etoposide, and cisplatin chemotherapy without the need for adjuvant radiotherapy. This represents a rare case of mature teratoma metastasizing to the choroid and one of very few reported testicular germ cell tumours to achieve normal or near normal visual acuity with chemotherapy alone despite severe macular disease at presentation.